Stress, Allostatic Load, and Psychosis: One Step Forward in Research But Where to Go Next? - Misiak, Błażej (Frontiers in Psychiatry, 2020)
Stress exposure leads to the activation of several biological mechanisms that have been termed allostasis. These processes enable adaptation to novel situations; however; their prolonged activation exerts systemic and detrimental effects called the allostatic load (AL). The AL concept represents one of useful paradigms to describe biological consequences of chronic stress that might lead to a number of disease outcomes. The AL index, which is a collective measure of cardiovascular, metabolic, neuroendocrine and immune dysregulations associated with stress exposure, has been found to predict morbidity and mortality in non-clinical populations. Consequently, it has been proposed that the AL concept might be a useful framework to describe biological consequences of chronic stress exposure in patients with psychotic disorders. This perspective article is an overview of studies investigating the AL index and its clinical correlates in patients with psychotic disorders. These studies have consistently reported elevated AL index in patients at the early and chronic course of psychosis. In addition, the AL index has been associated with a higher severity of positive and depressive symptoms, working memory impairments and lower general functioning. The article provides some critical appraisal of studies in this field and indicates several future directions for investigating the AL concept in psychosis.